Study of clinical and etiological profile of hypertensive emergencies in children admitted in pediatric emergency department - Kotapuri, Sumathi; Putta, Mahendranath; Chitgupikar, Sudharshanraj (International Journal of Contemporary Pediatrics, 2021)
Background: Hypertension (HTN) in children, all though an uncommon entity is associated with end-organ damage. With increasing prevalence of hypertension and obesity in children; hypertensive emergencies are also increasing over recent years and screening is must. The primary objective of this study was to determine the incidence of hypertensive emergencies, the clinical presentation and etiological diagnosis at different age groups and to access the real burden of primary hypertension in causing hypertensive emergencies in children. Methods: This study was a prospective, descriptive, analytical cohort study done on children attending the emergency department of pediatrics, government general hospital, a tertiary referral pediatric center attached to Kurnool medical college, Kurnool, over a period of 18 months i.e., from january2016 to June 2017. Data was collected in a pre-determined proforma after institutional ethical committee clearance and appropriate informed concerned. Results: Among 98 children with hypertension; 30 had hypertensive emergency. Incidence was 0.3%. Intrinsic renal and renal vascular causes were the commonest. Headache, dizziness and vomiting were the comment presentation. Half of them had encephalopathy. Younger children had more of secondary HTN and in children (older than 7 years) primary hypertension increased as did family history of hypertension. Conclusions: With increasing primary hypertension among older children, hypertensive emergencies are increasing. As most of the children with HTN are asymptomatic; detection of target organ damage is vital.